Effect of long-term use of treated wastewater and clean water mixtures on soil heavy metal accumulation: An assessment using pollution indices - Hasan Er (PLoS ONE, 2025)
The growing scarcity of clean water resources has driven increased interest in the use of treated wastewater (WW) as an alternative source for agricultural irrigation. While WW provides essential nutrients that can support plant growth and soil fertility, its long-term application may lead to the accumulation of heavy metals in soil, posing environmental and health risks. This study aimed to assess the effects of a four-year field experiment using different ratios of treated wastewater (WW) and clean water (CW) mixtures on soil heavy metal accumulation. Additionally, these effects were evaluated using widely accepted pollution indices, including the Contamination Factor (CF), Enrichment Factor (EF), Geoaccumulation Index (Igeo), and Pollution Load Index (PLI). A four-year field experiment was conducted using five irrigation regimes: W1 (100% WW), W2 (75% WW + 25% CW), W3 (50% WW + 50% CW), W4 (25% WW + 75% CW), and W5 (100% CW as control). The accumulation of Cr, Ni, Cu, Zn, Cd, Fe, and Pb was monitored. Results revealed that heavy metal concentrations increased with higher WW proportions and longer irrigation duration, but all levels remained below national and international regulatory limits. CF values approached moderate contamination levels for Pb, Fe, Zn, and Cd under W1, while Cr, Ni, and Cu indicated low contamination potential. EF values were mostly below 1.0, especially under mixed irrigation schemes, suggesting minimal anthropogenic enrichment. Igeo values were negative across all treatments, with the lowest values in the control group, classifying the soils as unpolluted. PLI values were consistently below 1.0, indicating an overall unpolluted status. The findings suggest that moderate blending ratios (25–50% WW) can limit heavy metal buildup while maintaining soil productivity. Therefore, the controlled use of treated wastewater in appropriate mixtures emerges as a promising approach for sustainable agricultural irrigation, balancing productivity with environmental protection.